2020
DOI: 10.3390/cells9020403
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Two Endothelial Cell Lines to Hydrogen Peroxide Toxicity: Relevance for In Vitro Studies of the Blood–Brain Barrier

Abstract: Oxidative stress (OS) has been linked to blood–brain barrier (BBB) dysfunction which in turn has been implicated in the initiation and propagation of some neurological diseases. In this study, we profiled, for the first time, two endothelioma cell lines of mouse brain origin, commonly used as in vitro models of the blood–brain barrier, for their resistance against oxidative stress using viability measures and glutathione contents as markers. OS was induced by exposing cultured cells to varying concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The relevance of oxidative stress and advantages/disadvantages of different experimental models used, especially in vitro, to study human pathophysiology was further stressed by O. Alamu et al, who analyzed the relevance of differential sensitivity of different endothelial cell lines to hydrogen peroxide used for in vitro studies of the blood-brain barrier (BBB) [8]. The authors found that even standardized and well-known cell lines can substantially differ in their antioxidant characteristics.…”
mentioning
confidence: 99%
“…The relevance of oxidative stress and advantages/disadvantages of different experimental models used, especially in vitro, to study human pathophysiology was further stressed by O. Alamu et al, who analyzed the relevance of differential sensitivity of different endothelial cell lines to hydrogen peroxide used for in vitro studies of the blood-brain barrier (BBB) [8]. The authors found that even standardized and well-known cell lines can substantially differ in their antioxidant characteristics.…”
mentioning
confidence: 99%
“…Additionally, this in-vitro human BBB model correlated well with human pharmacokinetic parameters 34 . We also have the advantage of the use of nonimmortalized cells, since immortalized cell lines have accumulated mutations, mycoplasma contamination, loss of BBB-like phenotype and authenticity complications 75,76 , resulting in varying BBB characteristics between intraspecies endothelial cell lines 77 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated how BBB endothelial cells respond to oxidative stress by exposing b.End3 and b.End5 cell lines to hydrogen peroxide. [ 59 ]. A decreasing viability of both cell line following exposure to increasing concentrations of hydrogen peroxide was shown.…”
Section: Cell Cultures As In Vitro Bbb Modelsmentioning
confidence: 99%